CLIMATE CHANGE ADAPTATION STRATEGIES IN URBAN AND REGIONAL PLANNING - Ajuluchukwu.C, Nwankwo; Jude Nnanugo Obidile; Chidozie Annastasia Ngozi (Journal of Geography, Regional Planning and Development, 2025)
Objective: The paper examined Climate Change Adaptation Strategies in Urban and Regional Planning in Nigeria. The paper concluded that integration of climate risk assessment into urban planning, development of green infrastructure and nature-based solutions, climate-resilient infrastructure and building design, sustainable urban transportation systems, land use planning and zoning regulations, community-based adaptation and public participation and policy integration and institutional strengthening are the Climate Change Adaptation Strategies in Urban and Regional Planning that can be adopted in Nigeria. One of the recommendations of the paper, in line with the outcomes, is that the federal, state and local planning bodies of Nigeria should incorporate physical and regional development plans with holistic climate risk assessment. Planners in urban and rural areas in Nigeria need to focus on green infrastructure development that employs natural processes in climate resiliency. Examples are are the creation of urban parks, green roof, community gardens, the restoration of wetlands, and planting trees along roads or around water bodies. With the cooperation of professional planning and engineering organizations, the Federal Ministry of Works and Housing should constitute and implement climate resilience building codes. Such standards would highlight on usage of durable materials, better drainage system, higher foundations in the flood prone regions and designs that use less energy. Other infrastructure amenities like roads, bridges and drainage facilities ought to be constructed with the in anticipation of the predicted alterations in rainfall intensity and temperature in order to guarantee long life span and safety. Urban planners should integrate transport and land use planning to promote compact city forms and reduce dependence on private cars. Encouraging public transportation use not only mitigates climate change but also improves urban air quality and energy efficiency. The federal and state governments should strengthen the enforcement of land use and zoning regulations to control unplanned urban expansion and settlement in high-risk zones.